The impact of casemix reimbursement on hospital revenue in Indonesia - Irwan Saputra,; Syed Mohamed Aljunid,; Amrizal Muhammad Nur, (Penerbit Universiti Kebangsaan Malaysia, 2020)
The objective of this study is to examine the impact of the casemix reimbursement on the hospital revenue three selected hospitals (Type B, C and D) reimbursed using 602 INA-CBG groups from 17,547 cases. The results of the study showed that the hospitals received 32.4% higher income when reimbursed with INA-CBG as compared to fee-for-service. Type D hospitals is the biggest gainer with 81.0% increased in income followed by Type B hospital that obtained 34.7% higher revenue. In conclusion, the use of INA-CBG as a prospective payment method has benefitted the hospitals by the increase in the revenues. It is hope that additional resources gained in this programme will allow the hospitals to provide optimum care to the population. It is recommended that the JKA management will use the INA-CBG casemix data to monitor the performance of the hospitals to ensure that quality and efficiency of the services provided to the population is continuously maintained.